2016
DOI: 10.1155/2016/4927530
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokines Th1, Th2, and Th17 Expression Profiling in Active Lupus Nephritis-IV: From a Southern Chinese Han Population

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by aberrant T cell immune response. Diffuse proliferative lupus nephritis (LN-IV) is the most common, severe, and active form of lupus nephritis. In this study, we investigated the production of Th1, Th2, and Th17 cytokines in prediction of active form of LN-IV. ProcartaPlex multiplex immunoassays panels were used for detection of serum Th1, Th2, and Th17 cytokines profiling. Th1 and Th17 cytokines (IL-18, IFN-γ, IL-12p70, IL-6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
(54 reference statements)
3
19
1
2
Order By: Relevance
“…We also found that 20.9% of the variance in the SLEDAI score was predicted by the Th1+Th17/Th2 ratio, increased IL‐10 and BMI (all positive) and the proinflammatory profile (negative) association. These findings are in line with recent studies reporting dysregulated Th1, Th2 and Th17 balances in SLE, with responses skewing towards Th17 and with higher Th1/Th2 and Th17/Th2 ratios 32 , 33 , 34 . This disruption is related to increased disease activity and organ damage 32 , 33 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that 20.9% of the variance in the SLEDAI score was predicted by the Th1+Th17/Th2 ratio, increased IL‐10 and BMI (all positive) and the proinflammatory profile (negative) association. These findings are in line with recent studies reporting dysregulated Th1, Th2 and Th17 balances in SLE, with responses skewing towards Th17 and with higher Th1/Th2 and Th17/Th2 ratios 32 , 33 , 34 . This disruption is related to increased disease activity and organ damage 32 , 33 .…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with recent studies reporting dysregulated Th1, Th2 and Th17 balances in SLE, with responses skewing towards Th17 and with higher Th1/Th2 and Th17/Th2 ratios 32 , 33 , 34 . This disruption is related to increased disease activity and organ damage 32 , 33 . Furthermore, visceral fat contributes to systemic immune activation and inflammation and this condition is a promoter of oxidative stress, 35 which all together are associated with disease progression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been suggested that the inappropriate regulation of Th17 cells may be a key event in the pathogenesis of rheumatoid arthritis and SLE (22). A number of studies have reported significantly higher serum levels of IL-17 and a higher frequency of IL-17-producing PBMCs in patients with SLE compared with normal individuals (6,7,13).…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells, producing IL-17 amongst other cytokines, have been demonstrated to serve a critical role in the pathogenesis of SLE (10)(11)(12). Th17 cells and multiple cytokines are involved in autoimmune diseases including SLE and LN (13).…”
Section: Introductionmentioning
confidence: 99%